Key to species of leafhopper genus Drabescoides Kwon & Lee (Hemiptera, Cicadellidae), with description of a new species from Southern China - Qu, Ling; Li, Hu; Dai, Ren-Huai (Zootaxa, 2014)
A new species Drabescoides complexa sp. nov. from Zhejiang and Fujian Provinces, China is described and illustrated, and can be distinguished by the unique aedeagus with pair of lamellae above a collar-shaped process on the shaft dorsal surface. A key to all species is given for identification based on the male genitalia along with a map showing the geographic distribution of the genus.